Constituição da memória institucional sobre sustentabilidade ambiental divulgada no âmbito da Universidade Federal do Pará - SILVA, Carla Patrícia Lima (Universidade Federal do Pará, 2024)
The Institutional Memory is constituted from the process of choice and selection of what was and is relevant to the history of an Institution, in this scenario the News Portal of the Federal University of Pará and the Institution's Academic Units is studied to identify this relationship . This research has as its guiding problem: How does the information on environmental sustainability disseminated within the scope of the Federal University of Pará constitute its Institutional Memory? To answer this question, the general objective is to analyze the dissemination of technical-scientific production on environmental sustainability generated within the scope of the Federal University of Pará for the constitution of Institutional Memory. As for the research methods and techniques, a single case study was carried out for data collection, and Content Analysis for the analysis of the data obtained. According to the cut delimited by the research, five sources of evidence were analyzed: Institutional Documents of the Federal University of Pará and the Institutional Communication Office; Analysis, based on data mining, of the pages of the News Portal of the Federal University of Pará and the websites of the Academic Units; Questionnaire answered by the administrators of these pages; Interview with the Director of the Communication Office of the University and Survey of Technical-scientific Production on the subject in the Institutional Repository of Theses and Dissertations of the Federal University of Pará. As a result, it was identified that the disclosures made through the Portal and the websites of the Academic Units are recognized by the University's management as an instrument in achieving the Institution's strategic management. There is dissemination of information on environmental sustainability on the University's websites, however the theme can be worked on further. The Communication Office recognizes the relevance of the theme and has been developing strategies for greater dissemination. As for the constitution of the Institutional Memory, although there is recognition that the Portal is a form of Constitution of the Institutional Memory of the Federal University of Pará, there is still no concern in the sense of structuring and maintaining it from this perspective, with the need to instrumentalize such a need. It was concluded that the University News Portal and the websites of the Academic Units can be considered as instruments in the constitution of the Institutional Memory of the Federal University of Pará, although currently they are not treated nor prepared to act in this way, however, they can become institutionalized places of memory.